Additional Benefits of Community Managed Forest: A Case Study of Champadevi Community Forest - Panthi, Bhanu B (Nepal Journal of Science and Technology, 2012)
This research attempts to identify the existing condition of the community managed forest based on the assumption that it will serve as a proxy for the condition of other forests in the mid hills region of Nepal. The research area has an atypical variation in altitude and diverse pattern of vegetation. This study mainly focuses on estimating carbon content in the forest and identifying the species that has more carbon storage capacity. The research signifies the role of forests in mitigation of ‘Global warming’ and ‘Climate change’ by storing carbon in tree biomass. These types of community based forest management programs are significant for their additional carbon sequestration through the avoidance of deforestation and degradation. The carbon sequestration have a significant contribution to environmental benefits, any shrinkage of forests have an enormous impact on CO2 emission with long term consequences. Thus, the development and expansion of community managed forests provide many benefits to the adjacent community and globally at large. DOI: http://dx.doi.org/10.3126/njst.v12i0.6490 Nepal Journal of Science and Technology 12 (2011) 127-32